Development of a Lagrange Mechanics E-Module Based on a Flipbook Pendulum Spring System - Putri, Faniya Nur Haryadi Eka; Hidayah, Hani Nur; Setiaji, Bayu (Jurnal Pendidikan Amartha, 2024)
This research is a type of Research and Development (R D) research that uses the 4D development model, namely Define, Design, Develop, Disseminate. This research produces a Lagrange Mechanics E-Module based on a flipbook pendulum spring system. The aim of this research is to produce a Lagrange Mechanics E-Module that is suitable for use as a learning medium for Analytical Mechanics. The data collection instrument used in this research is a questionnaire as a validation assessment for material experts and students, data analysis uses percentages with predetermined categories. The research sample was 14 Physics Education students. The validation results by material experts were 73% in the feasible category. The student response results were 85% in the very appropriate category. From these results, the Lagrange Mechanics E-Module is suitable for use with revisions as an alternative source of learning.